Anthobiomorphus, a new genus of Anthophagini Thomson, 1859 (Coleoptera: Staphylinidae: Omaliinae), with description of two new species from China, India and Nepal - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2020)
A new omaliine genus assigned to the Anthobium group of genera of the tribe Anthophagini Thomson, 1859, Anthobiomorphus Shavrin & Smetana, gen.n. is described. Two new species, A. rougemonti Shavrin & Smetana, sp.n. (China, Yunnan) and A. makranczyi Shavrin & Smetana, sp.n. (India: West Bengal and eastern Nepal) are described and illustrated. The main morphological features of the new genus and its taxonomic relationships with other related genera are briefly discussed. All available bionomic and distributional data and a key are presented.